Duplex ultrasound surveillance for asymptomatic deep venous thrombosis after total knee joint replacement - Khalil, Arwa Mohsun; Mohammed, Safwan Saeed (Journal of the Faculty of Medicine Baghdad, 2022)
Background: The prevalence of deep veins thrombosis, complicating total knee replacement in Asian countries, has not been fully appreciated in comparison to western countries as there are few studies on that. There is an important correlation between the evidence of deep veins thrombosis in the lower extremity and likelihood of   pulmonary embolism later one . Because of its noninvasive nature, duplex ultrasound has become one of the initial dependable modality for the cheek out of deep veins thrombosis after total knee replacement  . Therefore, this study was designed to evaluate the outcome of asymptomatic after total knee replacement by duplex ultrasound among Iraqi patients.Methods: This prospective study was conducted at AL-Shaheed Gazi AL-Hariri specialized Surgical Hospital, Radiology department, Ultrasound unit form from October 2009 to October 2010. Duplex ultrasound surveillance for asymptomatic deep venous thrombosis was done on 30 patients (13 females and 17 males ) who had underwent total knee replacement at day 5-7 postoperatively to investigate  the evidence  of deep venous thrombosis after total knee joint replacement among  Iraqi patients.Results: The percentage of deep veins thrombosis in this study was found to be 23.33%. Of these, 14% occurred in the popliteal and 86% occurred in the calf vein. Patients’ gender was not associated with significant higher incidence of deep veins thrombosis .Although the incidence of deep veins thrombosis  in patients aged more than 50 years was higher than in patients aged 30-50 years, it did not reach a statistically significant level. There was statistically significant relationship between obesity and the development of deep veins thrombosis. Patients with sedentary lifestyle showed higher incidence of deep veins thrombosis than patients with non-sedentary lifestyle and the difference reached a statistically significant level. The duration of the operation showed a significant correlation with  the incidence of deep veins thrombosis when the operation lasted more than 2 hours. In addition, there was higher incidence of deep veins thrombosis among smokers compered to non-smokers.Conclusion: The evidence of deep veins thrombosis was 22.33% in spite of anticoagulation coverage.  Also, duplex ultrasonography is suggested after total knee replacement, especially in patients who have other risk factors.